Procedural features of consideration of civil cases on compensation of the damage caused by illegal decisions, actions or inaction of the authority carrying out operatively-search activity, pre-judicial investigation, prosecutor’s office or court - Hnativ, Oksana; Manvelishvilі Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
Procedural features of consideration of civil cases on compensation of the damage caused by illegal decisions, actions or inaction of the authory carrying out operatively-search activity, pre-judicial investigation, prosecutor’s office or court The Constitution of Ukraine contains provisions that provide for the right of citizens to compensation for damage caused by illegal actions of officials in the exercise of their powers. The article examines some procedural features of civil cases for damages caused by illegal decisions, actions or omissions of the authority carrying out operational and investigative activities, pre-trial investigation, prosecution or court. The purpose of the article is to support the peculiarities of civil cases for compensation , illegal decisions, actions of inaction of the authority carrying out operational and investigative activities, pre-trial investigation, prosecutor’s office or court. The status of the state as a party in civil proceedings in this category of disputes is analyzed. It is concluded that, depending on the type of damage, a claim and non-claim method of dispute resolution can be used. Moral and material damage is subject to compensation. If the criminal proceedings are closed on the basis of an amnesty law or a pardon act, the right to compensation does not arise. It is important that the damage is reimbursed to the person in full, regardless of the fault of officials of the bodies carrying out operational and investigative activities, pre-trial investigation, prosecution and court. It is a guarantee that removes from the person whose rights have already been violated the obligation to prove the guilt or illegality of the actions of the authorities against him. The damage is compensated at the expense of the state budget of Ukraine. It should be noted that the exercise of a person’s right to compensation for damage caused by illegal decisions, actions or omissions of the body carrying out operational and investigative activities, pre-trial investigation, prosecution or court depends not only on its normative consolidation, but also on the existence of quality and effective implementation mechanism of this right.